2020
DOI: 10.1192/bjo.2020.24
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health and academic outcomes in first-year university students: Identifying prevention and early-intervention targets

Abstract: Background Although there is growing interest in mental health problems in university students there is limited understanding of the scope of need and determinants to inform intervention efforts. Aims To longitudinally examine the extent and persistence of mental health symptoms and the importance of psychosocial and lifestyle factors for student mental health and academic outcomes. Method Undergraduates at a Canadian university were invited to complete electronic surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 32 publications
2
86
1
8
Order By: Relevance
“…Consistent with work that has found that university students have high levels of mental health problems (e.g., Duffy et al 2020 ; Stallman 2010 ), the DASS mean score ( M = 18.27, SD = 11.78) was substantially higher than that for a representative sample of the general adult population of Australia ( N = 497, M = 8.30, SD = 9.83; Crawford et al 2011 , p. 9). The BMHI had a large positive correlation with the DASS ( r = 0.80, p < 0.001), indicating good convergent validity between these two measures.…”
Section: Resultssupporting
confidence: 85%
“…Consistent with work that has found that university students have high levels of mental health problems (e.g., Duffy et al 2020 ; Stallman 2010 ), the DASS mean score ( M = 18.27, SD = 11.78) was substantially higher than that for a representative sample of the general adult population of Australia ( N = 497, M = 8.30, SD = 9.83; Crawford et al 2011 , p. 9). The BMHI had a large positive correlation with the DASS ( r = 0.80, p < 0.001), indicating good convergent validity between these two measures.…”
Section: Resultssupporting
confidence: 85%
“…Rates of self-reported depression and anxiety in the United Kingdom are greater than the age-matched United Kingdom general population [ 5 ]. A growing body of research suggests that mental health difficulties worsen throughout the degree programme [ 6 , 7 , 8 ]. Whilst an increase in symptoms may not be caused by higher education itself, it is frequently suggested that the daily stressors associated with university life are a significant contributing factor [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has linked individual health risk factors to university student mental health, including both mental health disorders and psychological distress [ 10 , 11 , 12 ]. For example, in a cohort of students recruited at enrolment to a Canadian university ( n = 1530), health risk behaviors at enrolment predicted positive depression screen (substance use and sleep quality) and anxiety depression screen (sleep quality) at the end of the first year of university [ 10 ]. There has, however, been limited research exploring how clusters of health risk behaviors are linked with indicators of mental health among university students [ 9 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%